2021
DOI: 10.3390/ani11071949
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Integrated Approach for Monitoring Toxoplasmosis in Southern Italy

Abstract: Toxoplasmosis is a widespread worldwide zoonotic infection caused by the intracellular protozoan Toxoplasma gondii. This protozoan infection is considered one of the most important food-borne parasitic zoonoses globally. Beyond its impact on public health, toxoplasmosis has also important veterinary implications, because it causes miscarriage or congenital malformations in livestock with negative economic impacts. An integrated monitoring programme aimed to deepen the epidemiological data on toxoplasmosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…To our knowledge, only two further studies investigated the presence of T. gondii antibodies in lambs/young animals in Italy, and the reported positivity rate was very close to the one shown by our research (respectively, 41.7 and 41.0%) (6,10). As expected, we also found that young animals presented a significantly lower likelihood of being seropositive than adult sheep, with the former having fewer occasions of being exposed to T. gondii oocysts during their life.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…To our knowledge, only two further studies investigated the presence of T. gondii antibodies in lambs/young animals in Italy, and the reported positivity rate was very close to the one shown by our research (respectively, 41.7 and 41.0%) (6,10). As expected, we also found that young animals presented a significantly lower likelihood of being seropositive than adult sheep, with the former having fewer occasions of being exposed to T. gondii oocysts during their life.…”
Section: Discussionsupporting
confidence: 86%
“…In Italy, several surveys were performed in the past to assess the serological prevalence of T. gondii in the sheep population. Although differences due to the different analytical methods and study design are prevalent, the presence of T. gondii antibodies has been usually found in a relevant proportion of the tested sheep, implying that toxoplasmosis was not uncommon in this country (5)(6)(7)(8)(9)(10). However, most of these studies have been conducted on circumscribed territories (one province or region); therefore, their results (i.e., seroprevalence estimates and evaluation of the risk factors detection) should mainly refer to the specific studied areas.…”
mentioning
confidence: 99%
“…In the same region, a seroprevalence of 60.6% (77/127) was registered in adult dairy goats from 6/6 farms by MAT (cut-off 1:20) ( Mancianti et al, 2013 ). In Southern Italy, a study in the Campania region performed with the same ELISA kit and conditions used in the present study revealed seroprevalences of 56.7% (221/390) in sheep and 47.3% (114/241) in goats of different ages, with farm prevalences of 93.1% (27/29) and 80.8% (21/26) respectively ( Pepe et al, 2021 ). In France, a nationwide study based on meat juice analysis by MAT (cut-off: 1:6) showed seroprevalences of 15% in lambs and 81% in adult sheep ( Halos et al, 2010 ).…”
Section: Discussionsupporting
confidence: 57%
“…The incidence of acute human toxoplasmosis hospitalizations in the Campania region is of 0.72/per 100,000 inhabitants, as reported by hospital discharge records [ 46 ]. Most patients were aged less than 1 year of age, followed by adults between 25 and 44 years of age with no gender difference [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of acute human toxoplasmosis hospitalizations in the Campania region is of 0.72/per 100,000 inhabitants, as reported by hospital discharge records [ 46 ]. Most patients were aged less than 1 year of age, followed by adults between 25 and 44 years of age with no gender difference [ 46 ]. Health problems related to toxoplasmosis are, however, highly underestimated, as the parasite infection is linked to many chronic diseases [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%